Preparation method and application of catalyst for preparing hexamethylenediamine through nitrile hydrogenation based on polypyrrole-derived carbon fiber loaded metal nickel
By using a catalyst based on polypyrrole-derived carbon fiber-supported metal nickel in the nitrile hydrogenation reaction, the problems of short life of the existing catalyst and limited specific surface area are solved, and efficient and stable hydrogenation reactions and product purity are achieved, providing a new solution for the industrial production of hexanediamine.
Patent Information
- Application Number
- CN202411636083.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-15
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-11-15
AI Technical Summary
The existing catalysts for hydrogenation of nitrile compounds to prepare amine compounds, such as Raney-type catalysts, have poor anti-toxicity, poor mechanical properties, short catalyst life, and difficult to completely remove, resulting in difficulty in post-processing and filtration. The specific surface area of traditional catalyst support is limited and the pore size distribution is uneven, which limits the improvement of catalytic performance.
A nitrile hydrogenation catalyst based on polypyrrole-derived carbon fiber-supported metal nickel is used to prepare by hydrothermal method, and the porous and conductive properties of PPy-derived carbon fibers are used to achieve high stable dispersion and activity improvement of metal nickel, avoid the use of precious metals and reduce costs.
It realizes efficient and stable hydrogenation reaction, improves reaction conversion rate and product purity, has good stability and reusability, and provides a new solution for the industrial production of hexanediamine.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of preparing hexamethylenediamine by catalytic hydrogenation of nitrile compounds, and in particular to a preparation method and application of a nitrile hydrogenation catalyst for preparing hexamethylenediamine based on polypyrrole-derived carbon fiber loaded with metal nickel. Background Art
[0002] Amine compounds are an important class of intermediates, which play a wide range of roles in the synthesis of pesticides, medicines, textiles and polymer materials. Hexamethylenediamine contains two amino functional groups and has relatively active chemical properties. It can be condensed with adipic acid to produce polyhexamethylenediamine adipamide, also known as nylon 66. The new nylon 66 material can be applied to many directions such as photovoltaic power generation auxiliary materials, photovoltaic transmission materials, semiconductor packaging, and display component materials, and the market demand is large. At present, hexamethylenediamine is mainly obtained by hydrogenation of adiponitrile, and the partial hydrogenation of adiponitrile mainly includes gas phase method and liquid phase method catalytic hydrogenation, mainly including Raney type catalyst, non-supported nickel-based catalyst, supported nickel-based catalyst, etc.
[0003] Raney catalysts have been used in industry. CN1139392 and CN103977819 respectively disclose that Raney catalysts perform well in all aspects in the hydrogenation of nitrile compounds to prepare amine compounds. However, due to poor anti-toxicity and poor mechanical properties, Raney catalysts are easily broken during reaction stirring and liquid impact, and the catalyst life is short, resulting in difficulties in post-processing and filtering. It is difficult to completely remove it from the solution in industry, and the small particles produced by the breakage will also clog the reactor.
[0004] In recent years, PPy-derived carbon fibers have been explored for use in the field of catalyst carriers due to their porous, high specific surface area, and rich nitrogen doping. Metallic nickel, as an active component of hydrogenation catalysts, has the advantages of high catalytic activity and good stability. However, traditional catalyst carriers such as activated carbon have problems such as limited specific surface area and uneven pore size distribution, which limit the improvement of their catalytic performance. Therefore, the development of a catalyst based on PPy-derived carbon fibers loaded with metallic nickel is of great significance for improving the catalytic efficiency and product purity of nitrile hydrogenation reactions.
[0005] The present invention provides an adiponitrile / 6-aminocapronitrile hydrogenation catalyst and a preparation method thereof, which realizes an efficient and stable hydrogenation reaction by using PPy-derived carbon fiber as a carrier and combining the high catalytic activity of metal nickel. The catalyst not only improves the reaction conversion rate and product purity, but also has good stability and reusability, and provides a new solution for the industrial production of hexamethylenediamine.
[0006] Purpose of the Invention In view of the above technical problems, the present invention provides a method for preparing a catalyst for hydrogenating nitrile to produce hexamethylenediamine based on polypyrrole-derived carbon fiber loaded with metal nickel. The catalyst prepared by the method uses PPy-derived carbon fiber as a carrier, utilizes the rich nitrogen defects and pore structure of PPy to achieve metal capture and high-stability dispersion, and the conductive properties provided by the PPy-derived carbon layer itself promote electron transmission and improve catalyst activity; in addition, the use of noble metals as active components is avoided, the cost is low, the catalyst can still maintain high activity and selectivity after multiple reactions, and has good stability.
[0007] In order to achieve the above-mentioned object of the invention, the present invention provides the following specific technical solutions: A method for preparing a catalyst for preparing hexamethylenediamine by hydrogenation of nitrile based on PPy-derived carbon fiber loaded with metallic nickel, characterized in that the catalyst is prepared by a hydrothermal method, and the specific steps are as follows: (1) Preparation of PPy-derived carbon fiber precursor; (2) After dissolving the active nickel metal salt and the precipitant in water, adding PPy-derived carbon fiber as a precursor, hydrothermally stirring, centrifugally filtering, and low-temperature drying; (3) After high-temperature calcination, a highly dispersed nickel-loaded PPy catalyst was obtained.
[0008] In the present invention, in step (1), the preparation method of the PPy-derived carbon fiber precursor is: 1) Add hydrochloric acid to ultrapure water, add hexadecyltrimethylammonium bromide to the solution and stir until dissolved in an ice water bath; 2) Add ammonium persulfate to the above solution and stir until the solution turns milky white, then add pyrrole dropwise and stir at room temperature for 3-5 h to obtain black floccules; 3) Wash with anhydrous ethanol and ultrapure water in turn, filter for multiple times, place the obtained product in a vacuum drying oven, vacuum dry at 80-100°C for 24-30 hours, and grind to obtain black powder polypyrrole.
[0009] In the present invention, in step (2), the nickel metal salt is one of nickel chloride, nickel nitrate, nickel bromide and nickelous hydroxide, wherein the metal loading is 3%-10%.
[0010] In the present invention, in step (2), the precipitant is one or more of Na2CO3, NaOH, NH3·H2O, and urea, and the molar ratio of the precipitant to the loaded metal is 0.5-3:1.
[0011] In the present invention, in step (2), the hydrothermal temperature is 45-200° C., and the hydrothermal time is 2-12 h.
[0012] In the present invention, in steps (2) and (3), the drying temperature is 45-120°C, the calcination temperature is 600-800°C, the calcination atmosphere is argon atmosphere, and the calcination time is 2-8 h.
[0013] The catalyst prepared by the above preparation method is applied to the reaction of hydrogenating nitriles to generate hexylamine, and the specific steps are: adding the raw material liquid and the catalyst obtained after reduction into a reactor, reacting the raw material liquid and hydrogen under the catalytic action of the catalyst at a certain reaction temperature and pressure to generate hexamethylenediamine.
[0014] Preferably, the catalyst reduction temperature ranges from 400 to 700 °C, the reduction time is 2 to 6 h, and the reducing gas is H2 or H2 / N2.
[0015] Preferably, the nitrile compound is one of adiponitrile or 6-aminocapronitrile. Preferably, the raw material liquid is a nitrile-solvent mixed liquid, the solvent is one or more of methanol, ethanol, propanol, and isopropanol, wherein the mass concentration of the nitrile compound is 5-80 wt%.
[0016] Preferably, the hydrogenation reaction conditions are: reaction temperature is 60-130 ºC; reaction pressure is 2.0-5.0 MPa.
[0017] The reduced catalyst can also be first installed in a fixed bed for hydrogenation reaction. The method is to install the reduced catalyst in a fixed bed, introduce the raw material liquid, and react at a reaction temperature of 60-130 ºC and a reaction pressure of 2.0-5.0 MPa to generate hexamethylenediamine.
[0018] The beneficial effects of the present invention are: (1) The rich nitrogen defects and pore structure of PPy-derived carbon fibers are utilized to achieve metal capture and highly stable dispersion, and the conductive properties of PPy-derived carbon itself are used to promote electron transport and improve catalyst activity.
[0019] (2) Nickel is used as the loading metal, avoiding the use of precious metals and reducing process costs. DETAILED DESCRIPTION
[0020] The present invention is further described in detail below in conjunction with the embodiments. It should also be understood that the following embodiments are only used to further illustrate the present invention and cannot be construed as limiting the scope of protection of the present invention. The specific quality, reaction time and temperature, process parameters, etc. in the examples are only examples within the appropriate ranges. Some non-essential improvements and adjustments made by those skilled in the art according to the above content of the present invention all belong to the scope of protection of the present invention.
[0021] Unless otherwise specified, the raw materials and reagents in the following examples and comparative examples were purchased from commercial sources.
[0022] Example 1 Preparation of PPy-derived carbon fiber precursor: Add 90 ml of hydrochloric acid to 200 ml of ultrapure water, add 1 g of hexadecyltrimethylammonium bromide to the solution in an ice-water bath and stir for 10 min until dissolved, then add 1.5 g of ammonium persulfate to the above solution and stir for 20 min until the solution becomes milky white, then add 2.0 mL of pyrrole dropwise and stir at room temperature for 5 h to obtain black flocs, wash with anhydrous ethanol and ultrapure water in turn, filter several times, place the obtained product in a vacuum drying oven, vacuum dry at 80 °C for 24 h, and grind to obtain black powder polypyrrole PPy-derived carbon fiber.
[0023] Catalyst preparation: Weigh 0.006 mol nickel bromide and 0.02 mol Na2CO3 and dissolve them in 50 ml deionized water. After stirring evenly, add 10 g PPy-derived carbon fiber and continue stirring to obtain a uniform mixture. The mixture is then hydrothermally aged at 120 °C for 8 h. After cooling, filtering and drying, the precursor is heated to 700 °C at 5 °C / min in an argon atmosphere and calcined for 3 h to obtain a 3%-Ni / NC-700 catalyst.
[0024] Catalyst performance evaluation: First, the 3%-Ni / NC-700 catalyst was reduced in H2 atmosphere at 500℃ for 3 h to completely reduce the nickel metal. Then, a 20 wt% adiponitrile / isopropanol solution and 0.5 g of 3%-Ni / NC-700 catalyst were added to the autoclave, the autoclave was sealed, and the pressure was increased to 4.0 MPa after hydrogen was filled and replaced 3 times. The hydrogen bottle was opened to keep the pressure in the autoclave unchanged, and the temperature was raised. After the temperature in the autoclave rose to 100℃ and stabilized, the magnetic stirrer was turned on and the reaction timer was started. After reacting for 4 h, the reaction was cooled to room temperature and the pressure was released. The reaction products were analyzed by gas chromatography. The results are shown in Table 1.
[0025] Embodiment 2: Catalyst preparation: Weigh 0.01 mol nickel nitrate hexahydrate and 0.02 mol urea and dissolve them in 50 ml deionized water. After stirring evenly, add 10 g PPy-derived carbon fiber (prepared in Example 1) and continue stirring to obtain a uniform mixture. The mixture is then hydrothermally aged at 120 °C for 8 h. After cooling, filtering and drying, the precursor is heated to 700 °C at 5 °C / min in an argon atmosphere and calcined for 3 h to obtain a 5%-Ni / NC-700 catalyst.
[0026] Catalyst performance evaluation: 2.0 g of 5%-Ni / NC-700 catalyst was loaded into a fixed bed and reduced in a H2 atmosphere at 500 °C for 3 h. After the reduction was completed and the temperature dropped to the experimental temperature, 30 wt% 6-aminocapronitrile / ethanol solution was used as the raw material, the reaction temperature was 100 °C, the reaction pressure was 4 MPa, and the mass space velocity was set to 2.0 h -1 , hydrogenation was carried out under the condition that the molar ratio of hydrogen to adiponitrile was set to 30 to obtain a hexamethylenediamine reaction liquid, which was analyzed by gas chromatography. The results are shown in Table 1.
[0027] Embodiment 3: Catalyst preparation: Weigh 0.014 mol nickel chloride and 0.02 mol NH3·H2O and dissolve them in 50 ml deionized water. After stirring evenly, add 10 g PPy-derived carbon fiber (prepared in Example 1) and continue stirring to obtain a uniform mixture. The mixture is then hydrothermally aged at 120°C for 8 h. After cooling, filtering and drying, the precursor is heated to 700°C at 5°C / min in an argon atmosphere and calcined for 3 h to obtain a 8%-Ni / NC-700 catalyst.
[0028] Catalyst performance evaluation: First, the 8%-Ni / NC-700 catalyst was reduced in H2 atmosphere at 500℃ for 3h to completely reduce the nickel metal. Then, a 20 wt% adiponitrile / isopropanol solution and 0.5 g of 8%-Ni / NC-700 catalyst were added to the autoclave, the autoclave was sealed, and the pressure was increased to 4.0 MPa after hydrogen was filled and replaced 3 times. The hydrogen bottle was opened to keep the pressure in the autoclave unchanged, and the temperature was raised. After the temperature in the autoclave rose to 100℃ and stabilized, the magnetic stirrer was turned on and the reaction timer was started. After reacting for 4 h, the reaction was cooled to room temperature and the pressure was released. The reaction products were analyzed by gas chromatography. The results are shown in Table 1.
[0029] Embodiment 4: Catalyst preparation: Weigh 0.006 mol nickel bromide and 0.02 mol Na2CO3 and dissolve them in 50 ml deionized water. After stirring evenly, add 10 g PPy-derived carbon fiber (prepared in Example 1) and continue stirring to obtain a uniform mixture. The mixture is then hydrothermally aged at 120°C for 4 h. After cooling, filtering and drying, the precursor is heated to 700°C at 5°C / min in an argon atmosphere and calcined for 3 h to obtain a 3%-Ni / NC-700-2 catalyst.
[0030] Catalyst performance evaluation: First, the 3%-Ni / NC-700-2 catalyst was reduced in H2 atmosphere at 500℃ for 3h to completely reduce the nickel metal. Then, a 20 wt% adiponitrile / isopropanol solution and 0.5 g of 3%-Ni / NC-700-2 catalyst were added to the autoclave, the autoclave was sealed, and the pressure was increased to 4.0 MPa after hydrogen was filled and replaced 3 times. The hydrogen bottle was opened to keep the pressure in the autoclave unchanged, and the temperature was raised. After the temperature in the autoclave rose to 100℃ and stabilized, the magnetic stirrer was turned on and the reaction timer was started. After reacting for 4 h, the reaction was cooled to room temperature and the pressure was released. The reaction products were analyzed by gas chromatography. The results are shown in Table 1.
[0031] Embodiment 5: Catalyst preparation: Weigh 0.014 mol nickel chloride and 0.02 mol ammonia water and dissolve them in 50 ml deionized water. After stirring evenly, add 10 g PPy-derived carbon fiber (prepared in Example 1) and continue stirring to obtain a uniform mixture. The mixture is then hydrothermally aged at 120 °C for 8 h. After cooling, filtering and drying, the precursor is heated to 700 °C at 5 °C / min in an argon atmosphere and calcined for 5 h to obtain a 8%-Ni / NC-700-2 catalyst.
[0032] Catalyst performance evaluation: First, the 8%-Ni / NC-700-2 catalyst was reduced in H2 atmosphere at 500℃ for 3h to completely reduce the nickel metal. Then, a 15wt% adiponitrile / isopropanol solution and 0.5 g of 8%-Ni / NC-700-2 catalyst were added to the autoclave, the autoclave was sealed, and the pressure was increased to 4.0 MPa after hydrogen was filled and replaced 3 times. The hydrogen bottle was opened to keep the pressure in the autoclave unchanged, and the temperature was raised. After the temperature in the autoclave rose to 100℃ and stabilized, the magnetic stirrer was turned on and the reaction timer was started. After reacting for 4h, the reaction was cooled to room temperature and the pressure was released. The reaction products were analyzed by gas chromatography. The results are shown in Table 1.
[0033] Embodiment 6: Catalyst preparation: Weigh 0.01 mol nickel nitrate hexahydrate and 0.02 mol urea and dissolve them in 50 ml deionized water. After stirring evenly, add 10 g PPy-derived carbon fiber (prepared in Example 1), and continue stirring to obtain a uniform mixture; then hydrothermally age the mixture at 120 °C for 8 h. After cooling, filtering and drying, the precursor is heated to 800 °C at 5 °C / min in an argon atmosphere and calcined for 3 h to obtain a 5%-Ni / NC-800 catalyst.
[0034] Catalyst performance evaluation: 2.0 g of 5%-Ni / NC-800 catalyst was loaded into a fixed bed and reduced in a H2 atmosphere at 500 °C for 3 h. After the reduction was completed and the temperature dropped to the experimental temperature, 50 wt% 6-aminocapronitrile / ethanol solution was used as the raw material, the reaction temperature was 100 °C, the reaction pressure was 4 MPa, and the mass space velocity was set to 2.0 h -1 , hydrogenation was carried out under the condition that the molar ratio of hydrogen to adiponitrile was set to 30 to obtain a hexamethylenediamine reaction liquid, which was analyzed by gas chromatography. The results are shown in Table 1.
[0035] Embodiment 7: Catalyst preparation: Weigh 0.01 mol nickel nitrate hexahydrate and 0.02 mol urea and dissolve them in 50 ml deionized water. After stirring evenly, add 10 g PPy-derived carbon fiber (prepared in Example 1), and continue stirring to obtain a uniform mixture; then hydrothermally age the mixture at 120 °C for 8 h. After cooling, filtering and drying, the precursor is heated to 600 °C at 5 °C / min in an argon atmosphere and calcined for 3 h to obtain a 5%-Ni / NC-600 catalyst.
[0036] Catalyst performance evaluation: 2.0 g of 5%-Ni / NC-600 catalyst was loaded into a fixed bed and reduced in a H2 atmosphere at 500 °C for 3 h. After the reduction was completed and the temperature dropped to the experimental temperature, 30 wt% 6-aminocapronitrile / ethanol solution was used as the raw material, the reaction temperature was 100 °C, the reaction pressure was 4 MPa, and the mass space velocity was set to 2.0 h -1 , hydrogenation was carried out under the condition that the molar ratio of hydrogen to adiponitrile was set to 30 to obtain a hexamethylenediamine reaction liquid, which was analyzed by gas chromatography. The results are shown in Table 1.
[0037] Comparative Example 1: Catalyst preparation: The catalyst preparation was similar to that in Example 1, except that a step was added in which PPy was first calcined at 800° C. under an inert atmosphere and then loaded with nickel metal.
[0038] The catalyst performance evaluation was consistent with that in Example 1. The evaluation results are shown in Table 1.
[0039] Comparative Example 2: Catalyst preparation: The catalyst preparation was similar to that in Example 3, except that PPy was replaced with graphite carbon. The catalyst performance evaluation was consistent with that in Example 3. The evaluation results are shown in Table 1.
[0040] Comparative Example 3: Catalyst preparation: The catalyst preparation was similar to that in Example 2, except that PPy was replaced with carbon fiber. The catalyst performance evaluation was consistent with that in Example 2. The evaluation results are shown in Table 1.
[0041] Comparative Example 4: Catalyst preparation: The catalyst preparation was similar to that in Example 6, except that PPy was replaced with carbon nanotubes.
[0042] The catalyst performance evaluation was consistent with that in Example 6. The evaluation results are shown in Table 1.
[0043] By comparing the results of Example 1 with those of Comparative Example 1, it can be seen that the catalytic effect of the precursor loaded with nickel metal after PPy is first calcined to form carbon fibers is lower than that of the uncalcined precursor, which indicates that the carbon fiber structure formed by calcining PPy is not conducive to the loading of nickel metal; by comparing the results of Examples 2, 3, 6 and Comparative Examples 2-4, it can be seen that the nitrile hydrogenation catalyst with PPy-derived carbon fibers as carriers is more effective than other carbon carriers, because when other carbon carriers are loaded with nickel metal, the metal is prone to agglomeration, resulting in larger particle size and weak metal-carrier interaction, while the rich nitrogen defects and micro / mesoporous structure of PPy-derived carbon fibers are conducive to the capture and highly stable dispersion of metal precursors, so the catalyst prepared with other carbon carriers is weaker than that of PPy-derived carbon fibers.
[0044] Table 1. Evaluation results of the catalysts prepared in different examples for synthesizing hexamethylenediamine
[0045] Example 8 Recycling experiment of 5%-Ni / NC-700 catalyst in Example 2: First, 0.25 g of 5%-Ni / NC-700 catalyst was reduced in H2 atmosphere at 500℃ for 3h to completely reduce nickel metal. Then, 10 wt% adiponitrile / isopropanol solution and 0.25 g of 5%-Ni / NC-700 catalyst were added to the high-pressure reactor, the reactor was sealed, and hydrogen was filled with 1 MPa for replacement 3 to 5 times, and then placed in a heating jacket. When the temperature in the reactor rose to 100℃, the hydrogen pressure was increased to 4.0 MPa, the magnetic stirrer was turned on, and the reaction timer was started. After reacting for 4 h, it was cooled to room temperature, the reaction pressure was removed, and then the product was filtered and analyzed by gas chromatography. After the catalyst was recovered and dried and reduced, the above steps were repeated. The conversion selectivity of each use number is shown in Table 2: Table 2. Experimental results of recycling of 5%-Ni / NC-700 catalyst
Claims
1. A method for preparing a PPy-derived carbon fiber-supported nickel catalyst, characterized in that: The specific steps are as follows: (1) Preparation of PPy-derived carbon fiber precursor; (2) After dissolving the active nickel metal salt and the precipitant in water, adding the PPy-derived carbon fiber precursor, stirring for hydrothermal reaction, centrifugal filtration, and low-temperature drying; (3) After high-temperature calcination, a highly dispersed nickel-loaded PPy catalyst was obtained.
2. The preparation method according to claim 1, characterized in that: The preparation method of PPy-derived carbon fiber precursor is as follows: 1) Add hydrochloric acid to water, add hexadecyltrimethylammonium bromide to the solution in an ice-water bath and stir until dissolved; 2) Add ammonium persulfate to the above solution and stir until the solution turns milky white, then add pyrrole dropwise and stir at room temperature for 3 hours to obtain black floccules; 3) Wash with anhydrous ethanol and ultrapure water in turn, filter for multiple times, vacuum dry the obtained product, and grind it to obtain black powder polypyrrole.
3. The preparation method according to claim 1, characterized in that: The nickel metal salt is one of nickel chloride, nickel nitrate, nickel bromide and nickelous hydroxide, wherein the metal loading amount is 3%-10%.
4. The preparation method according to claim 1, characterized in that: The precipitant is one or more of Na2CO3, NaOH, NH3·H2O and urea, and the molar ratio of the precipitant to the loaded metal is 0.5-3:
1.
5. The preparation method according to claim 1, characterized in that: The hydrothermal temperature is 45-200°C and the hydrothermal time is 2-12h.
6. The preparation method according to claim 1, characterized in that: The drying temperature is 45-120°C, the calcination temperature is 600-800°C, the calcination atmosphere is argon atmosphere, and the calcination time is 2-8 h.
7. Use of the catalyst prepared by the preparation method according to any one of claims 1 to 6 in the hydrogenation reaction of nitrile compounds to produce hexamethylenediamine.
8. The use according to claim 7, characterized in that: The catalyst is first subjected to a reduction reaction before the nitrile hydrogenation reaction to generate hexamethylenediamine. The reduction reaction is to reduce the catalyst at a temperature range of 400-700° C., using H2 or H2 / N2 as the reducing gas, and the reduction reaction lasts for 2-6 hours.
9. The use according to claim 7, characterized in that: The nitrile compound is one of adiponitrile or 6-aminocapronitrile; during the hydrogenation reaction, the nitrile compound is dissolved in an alcohol solvent, and the solvent is one or more of methanol, ethanol, propanol, and isopropanol, wherein the mass concentration of the nitrile compound is 10-60 wt%.
10. The use according to claim 7, characterized in that: The hydrogenation reaction conditions are: reaction temperature is 60-130 ºC; reaction pressure is 2.0-5.0 MPa.
Citation Information
Patent Citations
Sulfur-carbon composite material with nitrogen-doped porous carbon nanofiber net-shaped structure, as well as preparation method and application of composite material
CN103700818A
Preparation method of adiponitrile hydrogenation catalyst
CN107812534A
Method for preparing nickel oxide-based compound semiconductor nano-fiber
CN109589982A
Ni / SiCNWs / CNFs flexible composite electrode material as well as preparation method and application thereof
CN110042408A
Preparation method of transition metal / nitrogen-doped carbon fiber electrocatalyst
CN110071300A
Cited By
Adiponitrile hydrogenation catalyst and preparation method thereof
CN120662315A